OPTIMALISASI PEMANFAATAN E-LEARNING EDLINK MELALUI SOSAKA (SOSIALISASI KOMUNIKATIF) - Fahmi, Merdila Nuril; Basra, Sri Meiweni; Ilham, Fadli; Hafid, Fathurrahman; Firdaus (Jurnal Inovasi Pendidikan dan Teknologi Informasi (JIPTI), 2025)
This study aims to determine the effectiveness of the SOSAKA (Socialization of Communication) program in optimizing the use of the Edlink e-learning platform in the Vocational Makeup Education Study Program, Indonesian Institute of the Arts (ISI) Padang Panjang. The background of this study is based on the low level of utilization of Edlink features optimally by students, especially in the context of online learning which is increasingly important after the pandemic. This study uses a descriptive quantitative method with a data analysis technique of respondent achievement level (TCR). The research sample consisted of 95 students from semester 1 to semester 6 who were selected by total sampling. Data was collected through a questionnaire covering five main indicators. The results showed that the average level of respondent achievement reached 74.6%, which is categorized as quite good. The highest indicator is the effectiveness of the SOSAKA program (83%), while the lowest indicator is interactive communication between lecturers and students (68%). These findings indicate that the SOSAKA program is effective in increasing students' awareness and skills in using Edlink, although there are still challenges in terms of interaction and utilization of advanced features. This study provides implications that interactive communication-based training such as SOSAKA needs to be continuously developed and integrated sustainably into academic activities. In addition, institutional support in the form of lecturer training, provision of facilities, and affirmative policies are also very necessary to encourage more optimal digital learning.